Kiss1 Inhibits the Proliferation of Nasopharyngeal Carcinoma Cells Via Activation of the LKB1/AMPK Pathway - Li, Tingting; Tian, Yong; Wang, Yixuan; Cui, Zhen; He, Zelai; Wu, Xiao; Zhang, Yajun; Jiang, Hao (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is a cancer that occurs in the nasopharynx. Infinite proliferation and distant metastasis are the main characteristics of NPC cells, and the main reason for the current failure of malignant tumor treatment. In this study, by integrating the immunohistochemical, cell transfection, western blot and real-time reverse transcriptase polymerase chain reaction (RT-PCR) analysis, we observed that the expression of KISS1 and its receptor gene (KISS1R) negatively related with the proliferation of NPC cells. Overexpression of the KISS1 genes in cells reduced cell proliferation, slow down the cell cycle, and increased apoptosis. Additionally, overexpression of these genes significantly increased Liver Kinase B1 (LKB1), phosphorylation of LKB1 and AMPK, indicated by Western blotting. Together, all of these results suggested for the first time that KISS1 and KISS1R suppress the proliferation of NPC cells by activating the LKB1/AMPK pathway, thus revealing a viable indicator for diagnosis of NPC in clinical practice.